Banquets, rations et offrandes alimentaires au Proche-Orient ancien : 10,000 ans d'histoire alimentaire révélée - Bonneterre, Daniel (Archaeopress Archaeology, 2021)
This text investigates food consumption in the ancient Near East. Archaeological discoveries and abundant textual documentation help reconstruct food supply to the cities of Mesopotamia and provide a better idea of the variety of products available. Some aspects of everyday life are presented in a new light, notably the social role of the banquet.